The Effect of Learning Management System with TRINGO Strategy on Technological Content Knowledge in Procedural Setting - Dedi Kuswandi; Muhammad Najmi Alwi Sinaga; Muhibuddin Fadhli; Fanny Kusdianti Nur Sya’bani; Zainullah Zainullah; Triyo Supriyatno; Winda Trimelia Utami (Jurnal Pendidikan Progresif, 2024)
The Effect of Learning Management System with TRINGO Strategy on Technological Content Knowledge in Procedural Setting. Objectives: This study aims to evaluate the effect of using the Learning Management System (LMS) combined with the TRINGO strategy on procedural learning outcomes (nglakoni) of educators who are also Muhammadiyah cadres in Malang City. TRINGO strategy, which consists of three stages, namely conceptual understanding (ngerti), emotional experience (ngrasa), and practical application (nglakoni) integrated in the use of LMS to improve the quality of education. Methods: This study used a quantitative approach with a one group pretest-posttest only quasi-experiment design. A total of 45 educators from 21 Muhammadiyah schools became respondents in this study. Data analysis was conducted using SPSS 27 through Wilcoxon test and multiple linear regression to test the proposed hypothesis.  Findings: The results showed that the use of LMS in TRINGO strategy significantly improved the concept understanding (ngerti) and emotional engagement (ngrasa) of the educators, with Z values of -5.982 and -6.214, respectively, and a significance value of 0.000. Furthermore, the combination of the LMS with the TRINGO strategy simultaneously had a significant effect on procedural learning outcomes (nglakoni), as indicated by an F-count of 94.550 (greater than the F-table of 3.21) and a coefficient of determination (R Square) of 0.818, indicating that 81.8% of the variation in procedural learning outcomes can be explained in this research. Conclusion: The conclusion of this study confirms that the integration of LMS with TRINGO strategy is effective in improving the procedural learning outcomes of cadres & educators, and provides important implications for the development of technology-based learning methods in Muhammadiyah educational environment. The results of this study are expected to contribute to the development of more effective learning models, especially in the context of cadre-based education in Indonesia. Keywords: LMS, TPaCK, tringo strategy, educational technology, muhammadiyah.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202485